FRI0428 RESULTS FROM A CROSS-SECTIONAL, OBSERVATIONAL STUDY TO ASSESS INADEQUATE PAIN RELIEF IN PATIENTS WITH KNEE AND/OR HIP OSTEOARTHRITIS IN CHINA. (2nd June 2020) - Zeng, X.; Leng, X.; Wei, K.; Tang, W. M.; Tang, C. H.; Tunceli, K.; Aggarwal, J.; Ramey, D.; Lozano, F.; Doshi, I.; Macahilig, C.; Odak, S.; et al.
Abstract : Background: Osteoarthritis (OA) of the knee and hip is a leading cause of disability worldwide, particularly due to the primary symptom of pain in the weight-bearing joints. There is limited data that characterizes patients who experience moderate to severe pain despite analgesic treatment in China. Objectives: This study estimates the real-world prevalence of inadequate pain relief (IPR) among patients with knee and/or hip OA who have been prescribed analgesic therapy and characterizes this patient population. The study was conducted in China, the Philippines, Thailand, Russia, and Mexico. This abstract presents results from China. Methods: This is a multinational, multi-site, cross-sectional, observational study. Physicians managing patients with OA were recruited and asked to enroll patients over 50 years of age with knee and/or hip OA who had been prescribed topical and/or oral pain medication for at least 30 days prior to study visit. Patients completed a one-time assessment of pain, function, and health-related quality of life (HRQOL) using patient reported outcome (PRO) instruments. Physicians abstracted data from patient charts. IPR was defined as an average pain score of >4/10 on Brief Pain Inventory Question #5 (average pain). Statistical tests including chi-square for categorical variables and Mann-Whitney Wilcoxon test for continuous variables were conducted to assess differences in demographic and clinical characteristics as well as PROs between patients with and without IPR. A multivariate regression analysis was conducted to assess the relationship between IPR and PROs. Results: 571 patients treated at 10 hospital centers in China were enrolled. 73% were female, the mean (SD) age was 62 (8.32) years. The number of years with OA ranged from less than one year to over 37 years, suggesting a broad sample of patients. Most patients were impacted by knee OA only (90%). Almost half (43%) of the study population met the definition of IPR. Patients with IPR tended to be older, have greater prevalence of obesity, have more comorbidities, and had longer disease duration. The majority (98%) of patients were receiving nonsteroidal anti-inflammatory drugs (NSAIDS), followed by chondroprotective medications (23%). However, more patients with IPR mentioned being dissatisfied with treatment (38% vs. 21%). After adjusting for covariates, patients with IPR reported worse HRQOL, more functional limitations, and reduced work productivity compared to patients without IPR. Conclusion: IPR is highly prevalent among individuals with knee and/or hip OA in China and is associated with decreased HRQOL and work productivity, impaired function, and treatment dissatisfaction. Developing awareness among healthcare professionals about the presence and potential impact of IPR is important for the ultimate improvement of OA patient management. Disclosure of Interests: Xiaofeng Zeng Consultant of: MSD Pharmaceuticals, Xiaomei Leng Consultant of: MSD Pharmaceuticals, Knightley Wei Employee of: Employed by MSD Pharmaceuticals (China), Wen Min Tang Employee of: Employed by MSD Pharmaceuticals (China), Cai Hua Tang Employee of: Employed by MSD Pharmaceuticals (China), Kaan Tunceli Shareholder of: Holds company stock at Merck Sharp & Dohme Corp., Employee of: Employed by Merck Sharp & Dohme Corp., Jyoti Aggarwal Consultant of: Merck & Co., Inc., Dena Ramey Shareholder of: Holds company stock at Merck Sharp & Dohme Corp., Employee of: Employed by Merck Sharp & Dohme Corp., Fidel Lozano Employee of: Merck & Co. salaried employee, Ishita Doshi Shareholder of: Holds company stock at Merck Sharp & Dohme Corp., Employee of: Employed by Merck Sharp & Dohme Corp., Cynthia Macahilig Consultant of: Consultant to Merck Sharp & Dohme Corp., Shardul Odak Consultant of: Consultant to Merck Sharp & Dohme Corp., Kelly Johnson Employee of: Employed by Merck & Co., Inc.